X-ray method for determination of mineral constituent in solid fuel - Mikhailov, I.F.; Baturin, A.A.; Mikhailov, A.I. (Functional Materials, 2014)
The method for determination of mineral constituent in solid fuel by the intensity ratio of Compton and Raleigh X-ray scattering peaks is proposed. The solid fuel is considered as a quasi-triple system of main phases C-SiO₂-Fe₂O₃ with evaluating the effect of accompanying admixtures on the analysis results. Measurements of mineral constituent have been carried out using coal standard samples prepared as powders with dispersion 60 μm. The method is intended for studying the systems of phases strongly different by average atomic number and requires no precision measurements of light element fluorescence.